Novel NHC precursors: synthesis, characterization, and carbonic anhydrase and acetylcholinesterase inhibitory properties - Aydin, Aktas; Taslimi, Parham; Gülçin, İlhami; Yetkin, Gok; Taslimi, Parham (Wiley, 2017)
Three series of imidazolidinium ligands (NHC precursors) substituted with 4-vinylbenzyl, 2-methyl-1,4-benzodioxane, and N-propylphthalimide were synthesized. N-Heterocyclic carbene (NHC) precursors were prepared from N-alkylimidazoline and alkyl halides. The novel NHC precursors were characterized by H-1 NMR, C-13 NMR, FTIR spectroscopy, and elemental analysis techniques. The enzymes inhibition activities of the NHC precursors were investigated against the cytosolic human carbonic anhydrase I and II isoenzymes (hCA I and II) and the acetylcholinesterase (AChE) enzyme. The inhibition parameters (IC50 and K-i values) were calculated by spectrophotometric method. The inhibition constants (K-i) were found to be in the range of 166.65-635.38nM for hCA I, 78.79-246.17nM for hCA II, and 23.42-62.04nM for AChE. Also, the inhibitory effects of the novel synthesized NHCs were compared to acetazolamide as a clinical CA isoenzymes inhibitor and tacrine as a clinical cholinergic enzymes inhibitor.
Keywords: Acetylcholinesterase; Carbonic anhydrase; Enzyme inhibition; Enzyme purification; N-Heterocyclic carbenes